Aromatase Inhibitor for Ovulation Induction: A Comparative Study Between Letrozole and Clomiphen Citrate in Anovulatory Infertile Women (Bangladesh Journal of Physiology and Pharmacology, 2010)
The study was designed to compare the effectiveness of Letrozole and clomiphen citrate in the treatment of anovulatorv infertility. Thirty patients were selected randomly who had anovulatorv infertility. In letrozole group, fifteen patients got 5-7.5 mg of letrozole orally and in clomiphen citrate group, 100-150 mg of clomiphen citrate was given orally for maximum of six cycles and in both the groups the drugs were started from day 3 -7 of the menstrual cycle. There were no significant differences between the age, duration and type of fertility. But statistically significant increase of follicular development in letrozole group (ñ=0.020). Mean endometrial thickness was 8.33±1.54 and 5.36±1.84 respectively in letrozole and in clomiphen citrate group (ñ =0.048). There was no significant difference in ovulation in both the groups but pregnancy was more (33.3%) with the letrozole group. Letrozole is an effective agent for ovulation induction. It can be used as an alternative to CC as a first-line of treatment for ovulation induction. DOI: 10.3329/bjpp.v25i1.5739Bangladesh J Physiol Pharmacol 2009; 25(1&2) : 10-12